2017
DOI: 10.1097/acm.0000000000001486
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Scholarly Concentration Program on Student Interest in Career-Long Research: A Longitudinal Study

Abstract: The impact of an SC program on change in career plans during medical school was analyzed. Program satisfaction, publication, and female gender were associated with increased intent to participate in career-long research depending on baseline interest in career-long research. Two ways to bolster the physician-scientist workforce are to improve satisfaction with existing SC programs and to formally support student publication. Future work to track outcomes of SC program graduates is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…We found that women placed significantly more importance on the development of a mentor relationship via the platform of the scholarly concentration programme than their male peers . In a separate study, we found that among students who entered medical school with high interest in career‐long research, women were more likely to graduate with enhanced interest compared to men . This is all very intriguing.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…We found that women placed significantly more importance on the development of a mentor relationship via the platform of the scholarly concentration programme than their male peers . In a separate study, we found that among students who entered medical school with high interest in career‐long research, women were more likely to graduate with enhanced interest compared to men . This is all very intriguing.…”
mentioning
confidence: 66%
“…We found similar results in our study of MD‐only students completing a scholarly project required for graduation. In our study, publication in medical school was associated with increased intent for career‐long research involvement measured between matriculation and graduation . It is important to highlight what completion of a research fellowship and publication represent to trainees: opportunities to build independence and scientific reputation.…”
mentioning
confidence: 71%
“…An ordinal logistic regression was used to test the association between interest change score, a peer-shared vs survey-shared video, and perception of entertainment [ 18 ]. Model 1 controlled for (1) whether the subject was an underrepresented minority in medicine (ie, Black, Pacific Islander, Native American), (2) gender, (3) baseline interest in clinical research, (4) baseline interest in a medical career, and (5) whether the recruiting friend was in the clinical or field research group.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that the medical school SP also impacts residency placements (Areephanthu et al, 2015;Radville et al, 2019) and decisions to pursue a career in research (Segal et al, 1990;Wolfson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%